Effect of PEG on the biodegradability studies of kenaf cellulose -polyethylene composites - Tajeddin, Behjat; Abdul Rahman, Russly; Abdullah, Luqman Chuah; Yusof, Yus Aniza; Ibrahim, Nor Azowa (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2009)
Several blends of cellulose derived from bast part of kenaf (Hibiscus cannabinus L.) plant, with different thermoplastics, low density polyethylene (LDPE) and high density polyethylene (HDPE), were prepared by a melt blending machine. Polyethylene glycol (PEG) was used as plasticizer. Biodegradability of these blends was measured using soil burial test in order to study the rates of biodegradation of these polymer blends. It was found that the cellulose/LDPE and cellulose/HDPE blends were biodegradable in a considerable rate. The bio-composites with high content of cellulose had higher degradation rate. In addition, biodegradability of the bio-composites made up using PEG was superior to those of the bio-composites fabricated without PEG, due to the improved wetting of the plasticizer in the matrix polymer. The results were also supported by the scanning electron microscopy (SEM).